Increased risk of carotid atherosclerosis for long-term exposure to indoor coal-burning pollution in rural area, Hebei Province, China. (December 2019) - Pang, Yaxian; Zhang, Boyuan; Xing, Dongmei; Shang, Jinmei; Chen, Fengge; Kang, Hui; Chu, Chen; Li, Binghua; Wang, Juan; Zhou, Lixiao; Su, Xuan; Han, Bin; et al.
Abstract: Smoky coal burning is a predominant manner for heating and cooking in most rural areas, China. Air pollution is associated with the risk of atherosclerosis, however, the link between indoor air pollution induced by smoky coal burning and atherosclerosis is not very clear. Therefore, we designed a cross-sectional study to evaluate the association of long-term exposure to smoky coal burning pollutants with the risk of atherosclerosis. 426 and 326 participants were recruited from Nangong, China and assigned as the coal exposure and control group according to their heating and cooking way, respectively. The indoor air quality (PM2.5, CO, SO2 ) was monitored. The association between coal burning exposure and the prevalence of atherosclerosis was evaluated by unconditional logistic regression analysis, adjusted for confounding factors. The inflammatory cytokines mRNAs (IL-8, SAA1, TNF-α, CRP) expression in whole blood were examined by qPCR. People in the coal exposure group had a higher risk of carotid atherosclerosis compared with the control (risk ratio [RR], 1.434; 95% confidence interval [95%CI], 1.063 to 1.934; P  = 0.018). The association was stronger in smokers, drinkers and younger (<45 years old) individuals. The elevation of IL-8 (0.24, 95%CI, 0.06–0.58; P   < 0.05), CRP (0.37, 95%CI, 0.05–0.70; P  < 0.05), TNF-α (0.41, 95%CI, 0.14–0.67; P   < 0.01) mRNAs expression in whole blood were positively related to coal exposure. Our results suggested long-term exposure to smoky coal burning emissions could increase the risk of carotid atherosclerosis. The potential mechanism might relate that coal burning emissions exposure induced inflammatory cytokines elevation which had adverse effects on atherosclerotic plaque, and then promoted the development of atherosclerosis. Graphical abstract: Image 1 Highlights: Smoky coal burning exposure could increase the risk of carotid atherosclerosis. The indoor air pollutants levels in coal burning room far exceeded the control. The inflammatory cytokines levels elevated in participants of coal exposure group. Abstract : Long-term exposure to coal combustion could increase the risk of carotid atherosclerosis: a cross-sectional study in rural area, China.